Quality Assessment of Systematic Review of the Bariatric Surgery for Diabetes Mellitus - Xinye Jin; Jinjing Wang; Xueqiong Li; Ping An; Haibin Wang; Wenfeng Mao; Qi Zhou; Yaolong Chen; Jie Wang; Kang Chen; Yiming Mu (Journal of Diabetes Research)
Objective. Using the AMSTAR tool, this study evaluated the quality of systematic reviews (SRs) that assessed the efficacy of bariatric surgery in diabetic patients. We aimed to identify studies that can be used as clinical references. Methods. Medline (via PubMed), EMBASE, Epistemonikos, Web of Science, Cochrane Library, CBM, CNKI, and Wanfang Data were systematically searched from inception to December 31, 2017. Two reviewers independently selected SRs and extracted data. Disagreements were solved by discussions or through consultation with a third reviewer. Reviewers extracted data (characteristics of included SRs, e.g., publication year, language, and number of authors) into the predefined tables in the Microsoft Excel 2013 sheet. Data were visualized using the forest plot in RevMan 5.3 software. Results. A total of 64 SRs were included. The average AMSTAR score was 7.4±1.7. AMSTAR scores of 7 (n=21, 32.8%) and 8 (n=14, 28.1%) were most common. The AMSTAR scores of SRs published before 2016 (n=46, 71.9%) were compared with SRs published after 2016 (n=18, 28.1%), and no significant differences were observed (MD=−0.79, 95% confidence interval (CI) -1.65-0.07, P=0.07). For SRs published in Chinese (n=17, 26.6%) compared to those published in English (n=47, 73.4%), the AMSTAR scores significantly differed (MD=0.21, 95% CI (-0.55, 0.97), P=0.59). For SRs published in China (n=33, 51.6%) compared to those published outside of China (n=31, 48.4%), significant differences in the AMSTAR scores were observed (MD=1.10, 95% CI (0.29, 1.91), P=0.008). For SRs with an author number≤6 (n=31, 48.4%) compared to SRs with authors≥6 (n=33, 51.6%), no significant differences were observed (MD=−0.36, 95% CI (-1.22, 0.50), P=0.41). For high-quality SRs published after 2016 (n=11, 17.2%) compared to other SRs (n=53, 82.8%), statistically significant differences were noted (MD=1.75, 95% CI (1.01, 2.49), P<0.00001). Conclusions. The number of SRs assessing the efficacy of bariatric surgery in diabetic patients is increasing by year, but only a small number meet the criteria to support guideline recommendations. Study protocols not being registered, grey literature not retrieved, incorporation of grey literature as exclusion criteria, and failure to evaluate publication bias and report a conflict of interest were the main causes of low AMSTAR scores.